Antibacterial Activity of Formulated Guava Leaf Extract (Psidium Guajava L.) Hand Wash Soap on Staphylococcus Aureus - Puteri, Cut Intan Annisa; Rani, Zulmai; Fauzi, Ziza Putri Aisyia; Ningtias, Anggitha; Dalimunthe, Gabena Indrayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
During the Covid-19 pandemic, the use of hand-washing soap increased. Hand-washing soap using natural ingredients as active ingredients is still not widely developed. One plant that has been proven to inhibit the growth of bacteria is guava leaves. This research aimed to formulate and test the antiseptic activity of liquid hand-washing soap from guava leaf extract. The research method used was laboratory experimental, with stages including; preparation of guava leaf extract, liquid soap formulation with a preparation concentration of FI 5%, FII 6%, FIII 7%, FIV 8%, then the physical properties of the soap will be tested to determine its quality and quality. Apart from the physical test, an antibacterial activity test was also carried out to determine the antibacterial effectiveness of the liquid hand wash soap formulation using the disc diffusion method to determine the diameter of inhibition or area of the inhibition zone. The preparation formula of 7% to 8% concentration of the preparation can inhibit growthStaphylococcus aureus. The diameter of the inhibition zone formed is included in the strong category. Based on research, it can be concluded that guava leaves have the potential to inhibit bacteria S. aureus, and evaluation of the preparations of all formulas shows stability and good characteristics. Each concentration has a good antibacterial effect, where the higher the extract concentration, the greater the diameter of the bacterial growth inhibition zones. aureusresulting from.